Measuring Values at Work: Extending Existing Frameworks to the Context of Work. (November 2020) - Albrecht, Simon; Marty, Andrew; Brandon-Jones, Nicholas J.
Personal values have been shown to be associated with a range of important psychological experiences, attitudes, and behaviors. Researchers and practitioners have, however, called for additional models and measures of employee values, specific to the context of work. Drawing from Schwartz's extensively studied model of personal values, this study aimed to develop a scale that researchers and practitioners can use to measure individual work values. Data from 2, 968 participants who were currently working or had previous work experience were analyzed using exploratory and confirmatory factor analyses. An 11-factor model, aligning closely with Schwartz's original personal values framework, yielded good fit. Furthermore, the 11 newly developed work values correlated significantly with Schwartz's generalized values, and multidimensional scaling broadly supported a configuration consistent with that previously proposed for general values. Overall, the research makes a contribution by extending Schwartz's extensively validated personal values framework to the context of work. The results support the psychometrics of a new measure of work values that will enable valid and reliable assessment of the important influence that work values can have on individual, team, and organizational outcomes. Practical implications, research limitations, and proposed future research directions are discussed.